Interpretation of sweep frequency response analysis traces on inter-turn short circuit fault - Nurul Farahwahida Md Yasid; A. A. Alawady; M. F. M. Yousof; S. Al-Ameri; M. S. Kamarudin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Sweep frequency response analysis (SFRA) is a reliable method for detection and diagnosis of faults in the active part of transformers. However, although SFRA is widely employed, the interpretation of SFRA signature is still a challenge and require experts to analyse them. This is due to lack of guideline and standard for SFRA signature interpretation and clarification. This paper presents the interpretation of SFRA signature by classification and quantification on inter-turn short circuit fault on the transformer winding. The short-circuited turns fault on HV winding phase “A” was practically simulated on three different units of three-phase transformers. The results of simulated fault are presented and discussed. A conclusion was drawn which provides the interpretation of the SFRA response due to inter-turn short circuit fault case by using a statistical indicator which is NCEPRI algorithm.